2016
DOI: 10.2174/1874325001610010662
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Periprosthetic Hip and Knee Joint Infections and the Economic Burden

Abstract: Periprosthetic Joint infection (PJI) following hip and knee replacements is an important complication causing major concern for patients, operating surgeons and healthcare systems. Therefore, a standardized definition of PJI is required to improve communication and allow for valid comparisons of various diagnostic and treatment strategies. This review summarizes the most commonly used definitions for PJI and the current consensus. It also highlights the economic burden related to PJIs and the importance of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Periprosthetic joint infection (PJI) is the most serious complication that lowers the quality of patients’ life by elevating the patients’ burden of cost and affecting the outcome of total joint arthroplasty (TJA) [13]. Delanois et al reported in 2017 that infection was the most common etiology for revision TKA (20.4%) in the USA [4].…”
Section: Introductionmentioning
confidence: 99%
“…Periprosthetic joint infection (PJI) is the most serious complication that lowers the quality of patients’ life by elevating the patients’ burden of cost and affecting the outcome of total joint arthroplasty (TJA) [13]. Delanois et al reported in 2017 that infection was the most common etiology for revision TKA (20.4%) in the USA [4].…”
Section: Introductionmentioning
confidence: 99%
“…4 In the United Kingdom, the cost for just 1 admission related to revision surgery for SSI is~22,000 pounds (~US$28,300). 9 A study from the United States estimated that the cost of SSIs following hip and knee arthroplasty has increased by US$246 million from 2001 to 2009, and is projected to exceed US$1.62 billion by 2020. 10 Even after appropriate management, as many as 60% of patients are not cured and require chronic treatment.…”
mentioning
confidence: 99%
“…The true cost of managing patients with complex joint infections is uncertain, though a study in Canada using gross costing methods estimated that the average cost for a hospital admission for an infected knee arthroplasty is more than CAD$20,000 (~US$15,280) 4 . In the United Kingdom, the cost for just 1 admission related to revision surgery for SSI is ~22,000 pounds (~US$28,300) 9 . A study from the United States estimated that the cost of SSIs following hip and knee arthroplasty has increased by US$246 million from 2001 to 2009, and is projected to exceed US$1.62 billion by 2020 10 .…”
mentioning
confidence: 99%
“…Periprothetische Hüftinfektionen sind schwerwiegende und medizinisch sowie ökonomisch herausfordernde Komplikationen in der Endoprothetik [ 1 , 6 , 22 , 26 ], deren Häufigkeit nach primärer Prothesenimplantation mit 0,5–2 % und bei Hüftprothesenrevisionen mit 4 % angegeben wird [ 8 , 10 , 28 ]. Bei weltweit zunehmender Anzahl an Primärimplantationen von Hüftprothesen ist von einem Anstieg periprothetischer Infektionen in den nächsten Jahren auszugehen [ 12 , 25 ].…”
Section: Hintergrund Und Fragestellungunclassified